2008
DOI: 10.3409/fb.56_3-4.133-137
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Activity Rhythm in Sheep and Goats Housed in Stable Conditions

Abstract: PICCIONE G., GIANNETTO C., CASELLA S., CAOLA G. 2008. Circadian activity rhythm in sheep and goats housed in stable conditions. Folia biol. (Kraków) 56: [133][134][135][136][137].The aim of this study was to establish the circadian rhythm of total activity in sheep and goats kept in housed conditions. For our study five Comisana breed sheep and five Maltese breed goats were kept in an individual box of 12 m under artificial 12/12 light/dark cycle for 14 days. We equipped the animals with Actiwatch-Mini, by mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 26 publications
8
14
0
Order By: Relevance
“…Quantification of vigilance states (Fig. 1I) showed that normal and CLN5 −/− Batten disease affected sheep exhibited diurnal behaviour consistent with previous reports of sheep housed under similar conditions (Tobler et al , 1991; Piccione et al , 2008) with significantly more wakefulness during day-time (μ norm = 81.4 ± 2.1%; μ CLN5 −/− = 89.0 ± 2.9%) than during night-time (μ norm = 55.3 ± 7.2%; μ CLN5 −/− = 67.3 ± 4.6%; normal: t = 4.590, df = 4, P = 0.010; CLN5 −/− : t = 8.470, df = 4, P = 0.001).…”
Section: Resultssupporting
confidence: 86%
“…Quantification of vigilance states (Fig. 1I) showed that normal and CLN5 −/− Batten disease affected sheep exhibited diurnal behaviour consistent with previous reports of sheep housed under similar conditions (Tobler et al , 1991; Piccione et al , 2008) with significantly more wakefulness during day-time (μ norm = 81.4 ± 2.1%; μ CLN5 −/− = 89.0 ± 2.9%) than during night-time (μ norm = 55.3 ± 7.2%; μ CLN5 −/− = 67.3 ± 4.6%; normal: t = 4.590, df = 4, P = 0.010; CLN5 −/− : t = 8.470, df = 4, P = 0.001).…”
Section: Resultssupporting
confidence: 86%
“…Our findings on daily activity patterns are also in agreement with previous studies. Locomotor activities of horses, goats, sheep and cows, housed individually in boxes, showed acrophase at the middle of the photoperiod (Bertolucci et al, 2008; Piccione, Caola & Refinetti, 2005; Piccione et al, 2008a; Piccione et al, 2008b; Piccione et al, 2010). An increase in relative activity from sunrise, reaching a peak toward midday, and then gradually decreasing in activity until sunset has also been described in wild Bactrian camels (Xue et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Daily rhythmicity of body temperature, cortisol and locomotor activity has been widely studied and described in many domestic animals, using different approaches, including diurnal index, conisor analysis and analysis of variance (Becker et al, 1985; Bohák et al, 2013; De Jong et al, 2000; Fulkerson, Sawyer & Gow, 1980; Giannetto et al, 2012; Martin et al, 2010; Piccione et al, 2010; Piccione et al, 2011; Piccione, Caola & Refinetti, 2002; Piccione et al, 2008b; Refinetti & Piccione, 2005; Thun et al, 1981). Disruption of daily rhythmicity can be associated with health problems, reduced life expectancy and altered well-being of the organism (Froy, 2011; Vitaterna, Takahashi & Turek, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Healthy cats treated with ocular hypotensive agents, and in those with uveitis and glaucoma, IOP rhythmicity is maintained (with higher values at night), even when animals are kept under dark conditions (Del Sole et al 2007, Ribeiro et al 2008b. Although the caprine species are considered to have daily habits (Piccione et al 2008b), studies evaluating periods longer than three days and performed under different conditions, seem to be necessary to clarify the importance of daily rhythmicity over IOP in this species.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in attempt to standardize intraocular pressure and tear secretion at different hours of the day and in different situations have been carried out in dogs, cats and horses (Gelatt & MacKay 1998, Hartley et al 2005, Del Sole et al 2007, Piccione et al 2008a, Ribeiro et al 2008b, Bertolucci et al 2009). Goats present a higher level of activity in the middle of the day (Piccione et al 2008b); for this reason, it is reasonable to hipothesize that intraocular pressure and tear secretion values as being lower during the evening.…”
Section: Introductionmentioning
confidence: 99%